Reduction of Intraocular Pressure by Additional Trabeculotomy Ab Externo in Eyes With Primary Open-angle Glaucoma. Issue 10 (October 2018) - Otsu, Yayoi; Matsuoka, Masato; Koshibu, Kayo; Miwa, Kayako; Kuro, Maki; Minamino, Keizo; Takahashi, Kanji; Nishimura, Tetsuya
Abstract : Purpose: The purpose of this study was to determine whether a second trabeculotomy (LOT) can reduce the intraocular pressure (IOP) in eyes with primary open-angle glaucoma (POAG) that had undergone an unsuccessful LOT as the initial surgery. Patients and Methods: LOT ab externo was performed as a second surgery on 37 eyes of 34 POAG patients who had undergone an unsuccessful LOT as the initial surgery. The main outcome measure was the postoperative IOPs, and surgical failures were defined as eyes with a post-LOT IOP>20 mm Hg. The eyes were divided into 3 groups; those that underwent LOT as both the initial and additional surgery (L-L group), those that underwent LOT as the initial surgery and combined LOT and cataract surgery (cLOT-IOL) as the additional surgery (L-cL group), and those that underwent cLOT-IOL as the initial surgery and LOT as the additional surgery (cL-L group). Results: The IOP was reduced after the additional LOT at postoperative 24 months in the L-L group from 20.0±3.0 mm Hg to 15.3±2.6 mm Hg ( P <0.001), the L-cL group from 19.8±1.6 mm Hg to 15.8±3.2 mm Hg ( P =0.029), and the cL-L group from 20.1±2.7 mm Hg to 15.5±2.3 mm Hg ( P =0.014). There were no differences in the preoperative and postoperative IOPs between the initial-operated and additional-operated eyes. The success rates were improved by the additional surgery in the L-L group ( P <0.001) and the L-cL group ( P =0.029), but the rate was worsened in the cL-L group ( P <0.001). Conclusions: These results indicate that LOT is a reasonable choice as an additional glaucoma surgery after failure of an initial LOT.